COVID-19: Famotidine, Histamine, Mast Cells, and Mechanisms - Malone, Robert W.; Tisdall, Philip; Fremont-Smith, Philip; Liu, Yongfeng; Huang, Xi-Ping; White, Kris M.; Miorin, Lisa; Moreno, Elena; Alon, Assaf; Delaforge, Elise; Hennecker, Christopher D.; Wang, Guanyu; et al. (Frontiers in Pharmacology, 2021)
SARS-CoV-2 infection is required for COVID-19, but many signs and symptoms of COVID-19 differ from common acute viral diseases. SARS-CoV-2 infection is necessary but not sufficient for development of clinical COVID-19 disease. Currently, there are no approved pre- or post-exposure prophylactic COVID-19 medical countermeasures. Clinical data suggest that famotidine may mitigate COVID-19 disease, but both mechanism of action and rationale for dose selection remain obscure. We have investigated several plausible hypotheses for famotidine activity including antiviral and host-mediated mechanisms of action. We propose that the principal mechanism of action of famotidine for relieving COVID-19 symptoms involves on-target histamine receptor H2 activity, and that development of clinical COVID-19 involves dysfunctional mast cell activation and histamine release. Based on these findings and associated hypothesis, new COVID-19 multi-drug treatment strategies based on repurposing well-characterized drugs are being developed and clinically tested, and many of these drugs are available worldwide in inexpensive generic oral forms suitable for both outpatient and inpatient treatment of COVID-19 disease.